Antimicrobial Screening of Some Medicinal Tree Species of Sikar District ofRajasthan (BioMedical Research in Microbiology (BMR Microbiology) (ISSN: 2349-4603), 2024)
Antimicrobial screening of ethyl ether and alcoholic extracts of leaves of three selected medicinal tree species growing in Sikar district of Rajasthan was carried out. Ailanthus excelsa, Pongamia pinnata and Salvadora oleoides showed positive reactions against bacterial pathogens i.e. Staphylococcus aureus, Escherichia coli and a fungal pathogen Candida albicans.